A Thrombin-Activatable Factor X Variant Corrects Hemostasis in a Mouse Model for Hemophilia A - Muczynski, Vincent; Verhenne, Sebastien; Casari, Caterina; Chérel, Ghislaine; Panicot-Dubois, Laurence; Gueguen, Paul; Trossaert, Marc; Dubois, Christophe; Lenting, Peter J.; Denis, Cécile V.; Christophe, Olivier D. (Thrombosis and Haemostasis, 2019)
Engineered recombinant factor X (FX) variants represent a promising strategy to bypass the tenase complex and restore hemostasis in hemophilia patients. Previously, a thrombin-activatable FX variant with fibrinopeptide-A replacing the activation peptide (FX-delAP/FpA) has been described in this regard. Here we show that FX-delAP/FpA is characterized by a sixfold shorter circulatory half-life compared with wild-type FX, limiting its therapeutical applicability. We therefore designed a variant in which the FpA sequence is inserted C-terminal to the FX activation peptide (FX/FpA). FX/FpA displayed a similar survival to wt-FX in clearance experiments and could be converted into FX by thrombin and other activating agents. In in vitro assays, FX/FpA efficiently restored thrombin generation in hemophilia A and hemophilia B plasmas, even in the presence of inhibitory antibodies. Expression following hydrodynamic gene transfer of FX/FpA restored thrombus formation in FVIII-deficient mice in a laser-induced injury model as well as hemostasis in a tail-clip bleeding model. Hemostasis after tail transection in FVIII-deficient mice was also corrected at 5 and 90 minutes after injection of purified FX/FpA. Our data indicate that FX/FpA represents a potential tenase-bypassing agent for the treatment of hemophilia patients with or without inhibitors.
Keywords: hemophilia; factor X; factor VIII